Disposition of orally administered a promising chemotherapeutic agent flavopiridol in the intestine. (June 2013) - Xia, Bijun; Liu, Xi; Zhou, Qiong; Feng, Qian; Li, Ye; Liu, Wei; Liu, Zhongqiu
<x xml:space="preserve">Abstract</x> Background: Flavopiridol (FLAP) is a promising chemotherapeutic agent undergoing clinical phase I and phase II trials, and a number of studies have elucidated its hepatic metabolism and biliary disposition. Methods: In present study, the intestinal disposition of orally administered FLAP was characterized through pharmacokinetic studies in rats as well as absorption and metabolism studies using a Caco-2 cell culture and four-site perfused rat intestinal models. Results: Pharmacokinetic results show that FLAP has high bioavailability (> 75%), long T1/2 (> 260 min), and short peak time (<20 min). In the Caco-2 cell culture model, the bidirectional permeability of FLAP was 0.47 × 10−5 cm/s to 1.53 × 10−5 cm/s and the efflux ratios were 3.27 and 2.17 at 10 and 30 μM, respectively. Apical loading of two P-glycoprotein (P-gp) inhibitors, cyclosporine A and verapamil, significantly increased the intracellular amount of FLAP and lowered its efflux ratio. In the four-site model, 10 and 40 μM FLAP perfusions were well absorbed at various regions of the intestine, and the biliary excretions of FLAP glucuronides were 1.60–2.84 nmol and 12.47–17.33 nmol, respectively. Conclusion: FLAP possesses high oral bioavailability and good absorption in the intestine, in which FLAP may be subjected to a P-gp efflux. Biliary excretion is the main elimination pathway for FLAP glucuronide and its enterohepatic cycling could be indicated.